Paradigma Mubadalah sebagai Solusi Relasi Keluarga dalam Menghadapi Tantangan Pemilihan Umum Tahun 2024 - Sri Furyani; Arif Suhaimi; M Munif Jazuli (Syakhsiyah Jurnal Hukum Keluarga Islam, 2024)
The Mubadalah paradigm emphasizes equality, justice, reciprocity, and cooperation between husband and wife in family relationships. It holds significant potential to address various social-political issues, including the challenges faced in the 2024 elections. This study aims to explore how the application of the Mubadalah paradigm in family life can contribute positively in facing the dynamics and complexities that emerge during the election process. This research uses a library research method, which involves activities related to data collection from library materials, reading, noting, and processing relevant books, research, and journals without requiring field research. Data collection was carried out through documentation, and for data analysis, content analysis was used. The results of the study show that Mubadalah, which prioritizes equality and mutual respect, can help create constructive dialogue between family members with differing political views. By applying the principles of Mubadalah, families can maintain harmony, overcome differences, and build resilience in facing political challenges without sacrificing family integrity.